2014
DOI: 10.4329/wjr.v6.i7.486
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear imaging in detection and monitoring of cardiotoxicity

Abstract: Cardiotoxicity as a result of cancer treatment is a novel and serious public health issue that has a significant impact on a cancer patient's management and outcome. The coexistence of cancer and cardiac disease in the same patient is more common because of aging population and improvements in the efficacy of antitumor agents. Left ventricular dysfunction is the most typical manifestation and can lead to heart failure. Left ventricular ejection fraction measurement by echocardiography and multigated radionucli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 45 publications
0
16
0
1
Order By: Relevance
“…The assessment of cardiotoxicity onset can be achieved by means of several approaches: echocardiographic evaluation of cardiac function (usually by measuring left ventricular ejection fraction, LVEF), imaging, and endomyocardial biopsy [ 7 , 8 ]. However, these techniques present important limitations, including low sensitivity, high invasiveness, elevated costs, and late detection of heart dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…The assessment of cardiotoxicity onset can be achieved by means of several approaches: echocardiographic evaluation of cardiac function (usually by measuring left ventricular ejection fraction, LVEF), imaging, and endomyocardial biopsy [ 7 , 8 ]. However, these techniques present important limitations, including low sensitivity, high invasiveness, elevated costs, and late detection of heart dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, most imaging studies have focused on the late stages of cardiotoxicity, either because imaging was prescribed after the clinical signs became evident, or because imaging failed to detect earlier signs. Nevertheless, a few studies have shown the capacity of nuclear imaging techniques to assess early cardiotoxicity associated with anthracyclines and trastuzumab 28 . Borde et al described a higher uptake of 2'-deoxy-2'-[ 18 F]fluoro-D-glucose (FDG) in the myocardium of patients treated with adriamycin, highlighting the capacity of positron emission tomography (PET) to detect a deregulation of myocardial metabolism induced by a cancer treatment 29 .…”
Section: Introductionmentioning
confidence: 99%
“…51 Gated blood-pool SPECT. Gated blood-pool SPECT allows for determination of LVEF, right ventricular EF, and wall motion abnormalities, 92 with excellent concordance with planar MUGA-derived LVEF.…”
Section: Single Photon Emission Computed Tomography (Spect)mentioning
confidence: 99%
“…51 Since clinical decisions for continuation or cessation of certain lifesaving oncologic therapy are currently based on accurate changes in LVEF, it is exceedingly important for the chosen imaging modality to be as accurate as possible, while maintaining minimal temporal variability, such that changes reflect true cardiotoxicity.…”
Section: Radiation-induced Heart Diseasementioning
confidence: 99%